Predicting proactive service performance: The role of employee engagement and positive emotional labor among frontline hospitality employees - Muhammad Zia Aslam; Mohammad Nazri Mohd Nor; Safiah Omar; Hasnun Anip Bustaman (Cogent Business & Management, 2020)
While previous research has improved our knowledge of how leadership influences employee behavior, the role of potential processes and contingencies in this relationship remains relatively unexplored. In the current study, based on the Self-determination Theory (SDT), we intend to contribute to this research by investigating whether employee engagement significantly plays the role of an intervening mechanism between employees' perceived interpersonal leadership of their supervisor and proactive service performance. Moreover, positive emotional labor (i.e., deep acting) is tested as a moderator to understand whether or not the strength of the relationship between employee engagement and employee proactivity is more for those who show more deep acting. Results of an online survey study among 438 frontline hospitality employees in Malaysia revealed that while employee engagement is a significant mediator in the relationship between interpersonal leadership and proactive service performance, positive emotional labor moderates the relationship between employee engagement and proactive service performance. Therefore, the findings of the current study provide initial evidence about how and for whom positive interpersonal leadership employee perceptions promote employee proactivity of frontline hospitality employees. Implications of the findings for the practice and research are discussed.
Keywords: 650; proactive service performance; leadership; engagement; positive emotional labor; hospitality employees; Malaysia